2010
DOI: 10.23972/det2010iss02pp88-100
|View full text |Cite
|
Sign up to set email alerts
|

Design de interface do ambiente virtual HyperCAL online

Abstract: A presente pesquisa objetiva propor uma metodologia que oriente o projeto de interface de ambiente virtual centrado no usuário que seja sistematizada como processo de produto com princípios de design de interação, considerando aspectos de usabilidade e ergonomia, de modo a favorecer o trabalho do usuário, permitindo a apropriação do conteúdo e a execução das tarefas através das funcionalidades do sistema. Para consecução do trabalho foram investigados: os elementos da experiência do usuário; as ferramentas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Thus, one of the important contributions made by the evaluators was to point out usability problems at the interfaces, which could confuse or distract users, suggesting significant changes to address the problems found. Other studies revealed similar suggestions, such as: insert explanations of charts and images that may not be entirely clear 15 , 25 , a scroll-bar for long texts 25 , changing the color of the interface 9 , 15 to light green, standardized links 25 , including an error message when users do not correctly fill out the registration screen, stopping wherever the error occurred 16 , and a page describing the icons 25 . In one study evaluating learning technology, evaluators had problems identifying some of the icons 7 , demonstrating how important it is that they be fully intuitive.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Thus, one of the important contributions made by the evaluators was to point out usability problems at the interfaces, which could confuse or distract users, suggesting significant changes to address the problems found. Other studies revealed similar suggestions, such as: insert explanations of charts and images that may not be entirely clear 15 , 25 , a scroll-bar for long texts 25 , changing the color of the interface 9 , 15 to light green, standardized links 25 , including an error message when users do not correctly fill out the registration screen, stopping wherever the error occurred 16 , and a page describing the icons 25 . In one study evaluating learning technology, evaluators had problems identifying some of the icons 7 , demonstrating how important it is that they be fully intuitive.…”
Section: Discussionmentioning
confidence: 78%
“…Usability problems related to these heuristics can reduce the interaction between the system and its users. Therefore, designers must pay attention when designing interfaces, making sure they are intuitive and easy for even an inexperienced user, avoiding additional effort in learning to use the system 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations